INTERPRETATION OF STATEMENTS RELATING TO THE JEWISH TRANSLATION IN CLASSICAL AND CONTEMPORARY COMMENTS - KAPLAN, Abdurrahim (Atlas Journal, 2021)
The most mentioned nation after believers in the Quran is the Jews. Jews are expressed in terms such as Ben-i Israel, Hâdû, Hûd, Yahud, Ehl-i Kitap, Ehl-i dhikr in the Quran. Although there are nuances in terms of meaning between these Words, all of them are used to refer to Jews. Many prophets whose names are mentioned in the Quran were sent to the Children of Israel. The histories, beliefs, culture and traditions of the Israelites are mentioned in many chapters, especially the Surah of Baqara. Although the blessings given to them are mentioned, their negative attitude towards their prophets, their distorting the Torah, their opposition to Allah’s orders, their punishment, their violation of the Saturday ban, their wrath and curse are among the issues mentioned in the Quran. It is not possible to cover all Jewish issues here. The topic has been addressed in many ways by other researchers. Here, we consider it appropriate to consider only the narrations about the violation of the Saturday ban, which causes the wrath and curse of Allah, by comparing them with classical and modern commentaries. In this study, it has been tried to determine whether the conversion of the Ashab-i-Sabt Jews into apes occurred physiologically.